Impact of purification on physicochemical, surface and functional properties of okra biopolymer. (October 2017) - Ghori, Muhammad U.; Mohammad, Mohammad Amin; Rudrangi, Shashi Ravi Suman; Fleming, Leigh T.; Merchant, Hamid A.; Smith, Alan M.; Conway, Barbara R.
Abstract: The functionality of plant-resourced biopolymers depends on their physicochemical properties. In addition, the extraction protocol and further processing conditions can significantly affect the effectiveness of biopolymer in diverse industrial applications. Therefore, the objective of this study was to investigate the impact of purification on chemical composition, molecular arrangement, solubility, swelling, erosion, wettability, quantitative wetting kinetics, surface energy and three-dimensional (3D) surface texture properties of okra biopolymer and its compacted form. FTIR and XRD results confirmed that the purification process had no effect on the molecular structural arrangement. The highest purity grade (bi-purified okra biopolymer) had the highest sugar content, solubility, matrix tablet swelling, wettability and surface energy, although the surface porosity and roughness of matrix tablet were low. Okra biopolymer showed pH-dependent solubility and the maximum solubility was achieved at pH 7.4. The mechanism of swelling of less-purified matrices was anomalous, where the rate of water diffusion and polymer relaxation was of the same magnitude, whereas bi-purified matrices showed diffusion-controlled swelling. Wetting was absorption-controlled and the bi-purified biopolymer had a high degree of wetting and surface energy. The extraction method, therefore, has a major influence on the properties and the subsequent drug delivery, biotechnology and food science applications for the biopolymer. Graphical abstract: Highlights: Three grades of okra biopolymer having varying degrees of purity were developed. FTIR and XRD results confirmed the suitability of purification process. Degree of purification was proportional to extent of swelling and solubility. Purification has a discernible impact on the surface properties. Development of analogous biopolymers may be possible using this extraction and purification protocol.